2011
DOI: 10.1016/j.surg.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine suppresses mouse Peyer's Patch T cell functions and induces bacterial translocation

Abstract: The gastrointestinal mucosa is an important route of entry for microbial pathogens. The immune cells of Peyer's patch (PP) compartments contribute to the active immune response against infection. Although local anesthetics are widely used in clinical practice, it remains unclear whether local anesthetics such as lidocaine affect PP T cell functions. The aim of this study was to examine if lidocaine has any effects on mouse PP T cell functions. To test this, freshly isolated mouse Peyer's patch T cells were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is difficult to translate those in vitro results to a clinical immunosuppressive effect of lidocaine because Jurkat cells are derived from the peripheral blood of a patient with T cell leukemia and express the uncontrolled characteristics of cancer cells ( 89 ). More physiologically, lidocaine also had an immunosuppressive effect on isolated mouse T cells derived from Peyer’s patches ( 90 ) and reduced the secretion of pro-inflammatory cytokines in freshly isolated peripheral blood T cells ( 88 ). In addition, lidocaine inhibited the differentiation of Th1 cell responses of mice dendritic cells ( 91 ).…”
Section: Effects On the Immune System: Implication For Malignant Disementioning
confidence: 99%
“…It is difficult to translate those in vitro results to a clinical immunosuppressive effect of lidocaine because Jurkat cells are derived from the peripheral blood of a patient with T cell leukemia and express the uncontrolled characteristics of cancer cells ( 89 ). More physiologically, lidocaine also had an immunosuppressive effect on isolated mouse T cells derived from Peyer’s patches ( 90 ) and reduced the secretion of pro-inflammatory cytokines in freshly isolated peripheral blood T cells ( 88 ). In addition, lidocaine inhibited the differentiation of Th1 cell responses of mice dendritic cells ( 91 ).…”
Section: Effects On the Immune System: Implication For Malignant Disementioning
confidence: 99%
“…In addition, the results of the present study revealed that intraoperative systemic lidocaine attenuated the apoptosis of PBL cells induced by surgical stressors. However, previous in vitro studies have demonstrated the opposite conclusions regarding cell proliferation (17,18) and apoptosis (19,20). This indicates that the protective effects of lidocaine on CMI in vivo are not directly due to its effects on lymphocytes, and the underlying mechanisms require further exploration.…”
Section: Discussionmentioning
confidence: 93%
“…10,12,13,70,84,191 Lidocaine has been shown to inhibit cell proliferation, cytokine production, and mitogen-activated protein kinase activation in T cells and upregulate regulatory T-cells that promote an antiinflammatory t-cell phenotype. 84,94,101,118 One study in mouse showed that release of antiinflammatory cytokine IL10 may be enhanced by lidocaine. 211 Questions remain as to how long the immunomodulatory effects of LAs persist after drug administration is complete.…”
Section: Local Anestheticsmentioning
confidence: 99%